Needs, expectations and doubt users of hormonal contraceptives - Galina B. Dikke (IP Berlin A.V., 2020)
Description. The review is presented by modern publications, reflecting the importance of high-quality patient counseling when choosing a method of contraception and the factors that influence it. The choice of combined oral contraceptive (COC) is determined by the need for reliable and safe contraception, expectations for an improved quality of life, and doubts about the frequency of side effects and effects on reproductive and somatic health. Modern COCs containing natural hormone (estradiol valerate), a new gestagen (dienogest) with a dynamic regime and a shortened hormone-free interval (2 days) satisfy the COC requirements of most women from menarche to menopause when contraception is required. An improvement in the profile of menstrual bleeding (a decrease in blood loss in 88% of users) and sexual functioning (increased libido, arousal, and maintaining the cyclical nature of sexual behavior) has been shown. Estradiol valerate does not affect metabolism, has a low risk of thromboembolic events (the adjusted risk of venous thromboembolism compared to other COCs is 0.4) and a low frequency of failure due to side effects (1.7%). This tool is characterized by high efficiency (adjusted Pearl index 0.42) and user satisfaction (78.180.2%). Conclusion. COCs with estradiol valerate/dinogest in 26/2 mode, fully satisfying the requirements of women for contraception, contributes to high adherence to it, that is, consistent and correct use, which contributes to the long-term use of the selected COC and ensures the quality of life of women for many years.